2008
DOI: 10.1107/s1600536808031292
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2-aminopyridine-κN1)silver(I) nitrate

Abstract: The asymmetric unit of the title compound, [Ag(C5H6N2)2]NO3, consists of one and a half each of both cations and anions, the other halves being generated by crystallographic inversion centres. One of the AgI atoms lies on an inversion center and one of the nitrate ions is disordered across an inversion center. Each AgI atom is bicoordinated in a linear geometry by two N atoms from two 2-amino­pyridine ligands. In the crystal structure, the cations and anions are linked into a two-dimensional network parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Table 2 shows a comparison between (I) and some related aminopyridine-Ag I compounds. Shorter Ag-N bond distances, wider N-Ag-N angles and hence weaker AgÁ Á ÁO interactions are reported for the related linear compounds [Ag(dmap) 2 ]PF 6 (Lin et al, 2008), [Ag(4-ampy) 2 ]NO 3 (Abu-Youssef et al, 2006a) and [Ag(2-ampy) 2 ]NO 3 (Fun et al, 2008) compared with those found in (I), while for the trigonal-planar and tetrahedral compounds [Ag 3 (NO 3 ) 2 (2-ampy) 4 ]NO 3 (Bowmaker et al, 2005) and {[Ag 4 (NO 3 ) 4 (3-ampy) 4 ]} n (Abu-Youssef et al, 2006b), longer Ag-N bond distances and narrower N-Ag-N angles are found. In the case of [Ag(dmap) 2 ]PF 6 (Lin et al, 2008), no interaction could be considered between the PF 6 À and Ag I ions, the shortest AgÁ Á ÁF distances being 3.007 (3) and 3.528 (6) Å .…”
Section: Commentmentioning
confidence: 94%
See 1 more Smart Citation
“…Table 2 shows a comparison between (I) and some related aminopyridine-Ag I compounds. Shorter Ag-N bond distances, wider N-Ag-N angles and hence weaker AgÁ Á ÁO interactions are reported for the related linear compounds [Ag(dmap) 2 ]PF 6 (Lin et al, 2008), [Ag(4-ampy) 2 ]NO 3 (Abu-Youssef et al, 2006a) and [Ag(2-ampy) 2 ]NO 3 (Fun et al, 2008) compared with those found in (I), while for the trigonal-planar and tetrahedral compounds [Ag 3 (NO 3 ) 2 (2-ampy) 4 ]NO 3 (Bowmaker et al, 2005) and {[Ag 4 (NO 3 ) 4 (3-ampy) 4 ]} n (Abu-Youssef et al, 2006b), longer Ag-N bond distances and narrower N-Ag-N angles are found. In the case of [Ag(dmap) 2 ]PF 6 (Lin et al, 2008), no interaction could be considered between the PF 6 À and Ag I ions, the shortest AgÁ Á ÁF distances being 3.007 (3) and 3.528 (6) Å .…”
Section: Commentmentioning
confidence: 94%
“…This type of ligand can coordinate to the metal center either via the ring N atom alone (as a monodentate ligand) or via both the ring N atom and the amine group N atom (as bridging and/or bidentate ligand). When 2-aminopyridine (2-ampy) reacts with AgNO 3 in water/ethanol solution, three compounds are formed with different stoichiometric ratios, namely [Ag(2ampy) 2 ]NO 3 (Fun et al, 2008), ]NO 3 and [Ag 3 (NO 3 ) 2 (2-ampy) 4 ]NO 3 (Bowmaker et al, 2005). In the case of 3-and 4-aminopyridine, only one compound is known for each, viz.…”
Section: Commentmentioning
confidence: 99%
“…The asymmetric unit of complex consists of one Ag+ central ion, one 2-NH2py ligand and one thiocyanate ligand. The Ag-N NH2py bond length (Table 3) shows a longer bond compared to the Ag-N 2-NH2py bond length in complexes [Ag(2-NH2py)3(NO3)] (Ag-N 2.141-2.179 Å) [15] and [Ag(2-NH2py)2](NO3) (Ag-N 2.1406-2.1413 Å) [13]. This is due to the formation of polymers which causes the molecules to be close each other and the bond angles are distorted in a smaller direction.…”
Section: Crystal Structure Determinationmentioning
confidence: 99%
“…Complexes with 2-,3-or 4-NH2py ligands show that NH2py tends to act as a monodentate ligand by binding to the central atom via the N pyridine ring. Complexes that have been reported such as [Ni(NCS)2(2-NH2py)2.C4H10O] [7], {∞[Cd(µ-SCN)2(4-NH2py)2]} [8], [Cu(SCN)2(x-NH2py)2] (x=2,3, or 4) [4], and [M(3-NH2py)2(dca)2] (M=Mn2+, Cu2+,Cd2+, or Co2+; dca = dicyanamide) [1,[9][10][11], [AgL(x-NH2py)2] [12][13][14][15][16] demonstrated the formation of polymer complexes via bridge formation by bidentate ligands such as dicyanamide, thiocyanate and azide. Several other complexes with monodentate ligands such as Cl¬ such as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation